DARLING (DIGITAL STORYTELLING) BASED ON DAYAKNESE FOLKLORE TO BOOST STUDENTS’ SPEAKING ABILITY - Yokie Prasetya Dharma; Ilinawati; Ferdinanda Itu Meo (EJI (English Journal of Indragiri) : Studies in Education, Literature, and Linguistics, 2023)
This research was conducted to find out whether Digital Storytelling - based Dayaknese folklore boost student participation in speaking ability. The method used was classroom action research. The population of this research was 22 students of the English education study program in the third semester. There are some aspects of speaking which focused on in this research, those aspects are pronunciation, vocabulary, fluency, comprehension, and grammatical accuracy.Based on the observation sheet, the overall activity ran well. Both of students and the lecturer played their roles well. The students were coming to be active in the classroom, discussing digital storytelling and the mechanism of publishing the video. The average score on the student test was 83,61, categorized as very good, it can be said digital storytelling is effective and can bust student motivation